Evaluation of Sleep Quality in Patients with COVID-19 after Discharge - Sareh Mohammadi; Fatemeh Aghakhanbeigi; Narges Hoseini; Sajad Noorian; Leili Yekefallah (Journal of Sleep Sciences)
Background and Objective: This study examines sleep quality in patients with coronavirus disease 2019 (COVID-19) after recovery, exploring demographic associations to inform post-discharge management and support.